1951
DOI: 10.1128/jb.62.4.499-511.1951
|View full text |Cite
|
Sign up to set email alerts
|

The Mechanism of the Heterolactic Fermentation: A New Route of Ethanol Formation

Abstract: The mechanism of ethanol production in bacterial fermentations has not been elucidated. Among the alcohol-producing bacterial systems available for study, the mixed ethanol-lactate fermentation characteristic of the heterofermentative lactic acid bacteria presents an interesting and apparently relatively simple case for experimentation. The major products of glucose fermentation by these organisms are lactic acid, ethanol, and carbon dioxide. Gayon and Dubourg (1901), Peterson and Fred (1920), and Nelson and W… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
43
0
1

Year Published

1968
1968
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 163 publications
(45 citation statements)
references
References 16 publications
1
43
0
1
Order By: Relevance
“…Smalley et al (19) have used molar growth yields to provide evidence of oxidative phosphorylation in S. faecalis lOCL. Homofermentative lactic acid bacteria such as S. faecalis (1,19), Lactobacillus plantarum (15), L. delbrueckii (3), and Saccharomyces cerevisiae (1) give molar growth yields with glucose (Yglucose) of about 21.0 g per mole, which is consistent with the YAT P value of 10.5 because of the known yield of 2 moles of ATP per mole of glucose in these fermentations. When the molar yield is greater than 20 to 21 g of cells per mole of glucose, it is likely that some pyruvate is further oxidized by a pathway that yields ATP in excess of 2 moles obtained from the Embden Meyerhof pathway.…”
supporting
confidence: 58%
“…Smalley et al (19) have used molar growth yields to provide evidence of oxidative phosphorylation in S. faecalis lOCL. Homofermentative lactic acid bacteria such as S. faecalis (1,19), Lactobacillus plantarum (15), L. delbrueckii (3), and Saccharomyces cerevisiae (1) give molar growth yields with glucose (Yglucose) of about 21.0 g per mole, which is consistent with the YAT P value of 10.5 because of the known yield of 2 moles of ATP per mole of glucose in these fermentations. When the molar yield is greater than 20 to 21 g of cells per mole of glucose, it is likely that some pyruvate is further oxidized by a pathway that yields ATP in excess of 2 moles obtained from the Embden Meyerhof pathway.…”
supporting
confidence: 58%
“… Acetoin (3‐hydroxy‐2‐butanone) may be reduced to butane‐2,3‐diol by the action of butanediol dehydrogenase: CH 3 ·CO·CH(OH)·CH 3 + NADH + H + →CH 3 ·CH(OH)·CH(OH)·CH 3 + NAD + [79]. …”
mentioning
confidence: 99%
“…Glucose dissimilation under anaerobiosis by Leuconostoc mesenteroides species was first established by DeMoss et al 7 and confirmed by further studies.2,&-'0 These heterofermentative microorganisms catabolize glucose via the pentose phosphoketolase pathway yielding essentially equimolar amounts of D-lactate, carbon dioxide, and ethanol under anaerobiosis.…”
Section: Introductionmentioning
confidence: 93%